Comparative Evaluation of Heavy Metals in Patients with Rheumatoid Arthritis and Healthy Control in Pakistani Population - Shazia IRFAN; Asima RANI; Naila RIAZ; Muhammad ARSHAD; Syed KASHIF NAWAZ (Iranian Journal of Public Health, 2017)
Background: Exposure to heavy metals in development of many diseases has been investigated previously, specially created by oxidative stress. The etiology of Rheumatoid arthritis (RA) is still not fully understood but oxidative stress created by heavy metals may have role in development of RA. The aim of present study was to compare serum level of heavy metals in RA and healthy control individuals.